Association between MUC1 gene polymorphism and expected progeny differences in Nelore cattle (Bos primigenius indicus) - Souza, Fabio Ricardo Pablos de; Vozzi, Pedro Alejandro; Vila, Reginaldo Aparecido; Boligon, Arione Augusti [UNESP]; Galerani, Marli Aparecida Vani; Lobo, Raysildo Barbosa; Martelli, Lucia Regina (Sociedade Brasileira de Genética, 2010)
MUC1 is a heavily glycosylated mammalian transmembrane protein expressed by mucosal secretory tissues for both protection against microbial infection and lubrication. An important characteristic of MUC1 is its variable number of tandem repeats (VNTR) containing several sites for O-glycosylation. VNTR length has been associated with many human diseases and with certain economically important traits in domestic ruminants. The aim of the present study was to correlate the length of MUC1 gene VNTR with expected progeny differences (EPDs) obtained for growth, fertility and carcass traits. Five alleles were identified, with alleles containing short VNTRs being more frequent than those with long, thereby demonstrating that Brazilian Nelore cattle are characterized by high frequencies in short MUC1 VNTRs. Statistical analyses revealed there to be no significant association between VNTR length and EPDs for weight at 120 days (W120), scrotal circumference at 365 (SC365) and 450 (SC450) days, age at first calving (AFC), and rib eye area (REA).
Keywords: Beef cattle; Molecular marker; Productive traits; quantitative trait locus